2007
DOI: 10.1158/1541-7786.mcr-06-0353
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 Mucin Potentiates Pancreatic Tumor Cell Proliferation, Survival, and Invasive Properties and Interferes with Its Interaction to Extracellular Matrix Proteins

Abstract: MUC4, a transmembrane mucin, is aberrantly expressed in pancreatic adenocarcinomas while remaining undetectable in the normal pancreas. Recent studies have shown that the expression of MUC4 is associated with the progression of pancreatic cancer and is inversely correlated with the prognosis of pancreatic cancer patients. In the present study, we have examined the phenotypic and molecular consequences of MUC4 silencing with an aim of establishing the mechanistic basis for its observed role in the pathogenesis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
205
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(231 citation statements)
references
References 52 publications
21
205
0
5
Order By: Relevance
“…1). This supports the aforementioned observations and indicates the important role of the MUC4 in pancreatic adenocarcinoma development and progression (21,23,24). A recent study has demonstrated the presence of a highly conserved miR-150 binding site at the 3'-UTR of MUC4 and that its direct interaction with miR-150 downregulated the endogenous MUC4 protein expression levels, as shown in Table I (25).…”
Section: Mir-150 In Pancreatic Cancersupporting
confidence: 81%
“…1). This supports the aforementioned observations and indicates the important role of the MUC4 in pancreatic adenocarcinoma development and progression (21,23,24). A recent study has demonstrated the presence of a highly conserved miR-150 binding site at the 3'-UTR of MUC4 and that its direct interaction with miR-150 downregulated the endogenous MUC4 protein expression levels, as shown in Table I (25).…”
Section: Mir-150 In Pancreatic Cancersupporting
confidence: 81%
“…In this paper, we showed that MUC4 induces an increase in mitochondrial mass without changing the apoptotic index. However, in our MUC4 knockdown cell line model, we showed that endogenous overexpression of MUC4 is preventing apoptosis of the CD18/HPAF pancreatic cancer cells after 48 -72 h serum starvation (Chaturvedi et al, 2007). The lack of detection of any significant change in apoptosis and PARP activity in mini-MUC4-transfected cells might be due to the fact that apoptosis was induced by serum starving the cells for less than 24 h. The shorter duration of serum starvation was applied owing to the reason that Panc1 cells and their derivatives cannot survive for more than 24 h in serum-free media.…”
Section: Discussionmentioning
confidence: 68%
“…Using MUC4-knockdown and overexpression pancreatic cancer cell models, we have shown that MUC4 potentiates pancreatic tumour cell growth and metastasis by altering the behavioural properties of the tumour cells (Singh et al, 2004;Chaturvedi et al, 2007;Moniaux et al, 2007). Recently, the anti-apoptotic function of MUC4 in pancreatic cancer cells has been observed in our laboratory .…”
Section: Discussionmentioning
confidence: 94%
“…Recently, we have shown that the overexpression of MUC4 in mouse embryonic fibroblast cells confers oncogenic transformation . In addition, studies by overexpression and down-regulation of MUC4 in various pancreatic cancer cells showed its involvement in the development and progression of pancreatic cancer (Singh et al, 2004;Chaturvedi et al, 2007;Moniaux et al, 2007). Importantly, our recent studies have revealed that MUC4 interacts with HER2, a member of epidermal growth factor (EGF) receptor family and regulates its expression by post-translational mechanisms (Chaturvedi et al, 2008).…”
mentioning
confidence: 99%